2005
DOI: 10.1111/j.1600-0765.2005.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis heat shock protein vaccine reduces the alveolar bone loss induced by multiple periodontopathogenic bacteria

Abstract: We concluded that P. gingivalis HSP60 could potentially be developed as a vaccine to inhibit periodontal disease induced by multiple pathogenic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…Therefore, they are frequently used to produce subunit vaccines. Numerous studies have shown the efficiency of immunisation with HSP family proteins in the induction of a protective immune response against pathogens (Kaufman et al 1990;Mannicki 1995;Noll and Autenrieth 1996;Lee et al 2006;Bansal et al 2010). It has been demonstrated that H. somni rHsp60 induces an immune response in SPF mice .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are frequently used to produce subunit vaccines. Numerous studies have shown the efficiency of immunisation with HSP family proteins in the induction of a protective immune response against pathogens (Kaufman et al 1990;Mannicki 1995;Noll and Autenrieth 1996;Lee et al 2006;Bansal et al 2010). It has been demonstrated that H. somni rHsp60 induces an immune response in SPF mice .…”
Section: Discussionmentioning
confidence: 99%
“…They are potent inducers of the immune system, inducing both innate and adaptive immune responses. 27,28 Many microbial HSPs are reported to be dominant antigens that elicit host immune responses to a variety of pathogens [29][30][31][32][33][34] and act as effective adjuvants. 35 Previously, we developed recombinant (r) Hsp 60 (GroEL) and rHsp70 (DnaK) from Salmonella enterica serovar Typhi, and we reported that these candidate vaccine molecules stimulate both arms of immunity against S. Typhi and S. typhimurium infection in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Assays for a qualified target, such as the P18 subpeptides, would indicate/ justify aggressive adjunct periodontitis treatment and provide a simple method for monitoring that treatment. In the long term, these subpeptides might be found to be effective vaccine candidates (21). Since the P18 subpeptides appear to be unique antigens, they could be used as vaccines without fear of inducing inappropriate responses to human Hsp90.…”
Section: Discussionmentioning
confidence: 99%